Vegetation change across the Drake Passage region linked to late Eocene cooling and glacial disturbance after the Eocene–Oligocene Transition - Thompson, Alasdair; Salzmann, Ulrich; López-Quirós, Adrián; Bijl, Peter K.; Hoem, Frida S.; Etourneau, Johan; Sicre, Marie-Alexandrine; Roignant, Sabine; Hocking, Emma; Amoo, Michael; Escutia, Carlota (Climate of the Past, 2022)
The role and climatic impact of the opening of the Drake Passage and how it affected both marine and terrestrial environments across the Eocene–Oligocene transition (EOT ∼34 Ma) period remains poorly understood. Here we present new terrestrial palynomorph data compared with recently compiled lipid biomarker (n-alkane) data from Ocean Drilling Program (ODP) Leg 113, Site 696, drilled on the margin of the South Orkney Microcontinent (SOM) in the Weddell Sea, to investigate changes in terrestrial environments and palaeoclimate across the late Eocene and early Oligocene (∼37.6–32.2 Ma). Early late Eocene floras and sporomorph-based climate estimates reveal Nothofagus-dominated forests growing under wet temperate conditions, with mean annual temperature (MAT) and precipitation (MAP) around 12 ∘C and 1802 mm respectively. A phase of latest Eocene terrestrial cooling at 35.5 Ma reveals a decrease in MAT by around 1.4 ∘C possibly linked to the opening of the Powell Basin. This is followed by an increase in reworked Mesozoic sporomorphs together with sedimentological evidence indicating ice expansion to coastal and shelf areas approximately 34.1 Myr ago. However, major changes to the terrestrial vegetation at Site 696 did not take place until the early Oligocene, where there is a distinct expansion of gymnosperms and cryptogams accompanied by a rapid increase in taxon diversity and a shift in terrestrial biomarkers reflecting a change from temperate forests to cool temperate forests following 33.5 Ma. This surprising expansion of gymnosperms and cryptogams is suggested to be linked to environmental disturbance caused by repeat glacial expansion and retreat, which facilitated the proliferation of conifers and ferns. The timing of glacial onset at Site 696 is linked to the global cooling at the EOT, yet the latest Eocene regional cooling cannot directly be linked to the observed vegetation changes. Therefore, our vegetation record provides further evidence that the opening of the Drake Passage and Antarctic glaciation were ...